Learning Autonomy in English Speaking Skill - Amini, Wahyal; Kusumaningsih, Citra; Sari, Dian Shinta (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2021)
The study aimed to find out kinds and the effects of students’ learning autonomy. This research is qualitative research. The subject of study is 11th graders Science 4 SMAN 1 Mempawah Hilir. To obtained data, researcher used indirect and direct method, there are questionnaire and interview guidelines. The analyzed data obtained from questionnaire by grouping kinds of students’ learning autonomy then to know the effects, researcher conducted interviews to 8 students. The results are vocabulary notebook is a kind of learning autonomy sometimes used (17.9%) while the most frequently used is English songs (63%). The effects they feel are gain new vocabulary, familiar with environment that uses English, enhances confidence and fluency. In conclusion, there are some kinds of learning autonomy students often do, like using vocabulary notebooks and Youtube, listening English podcasts, audiobooks or English dramas and English songs, speaking exercise focuses on fluency, not on grammar, talking to myself, playing English games, and watching English movies or TV programs. From those kinds of learning autonomy, students can improve speaking skill in terms of vocabulary and fluency and can be recommendations to improve speaking skill. In addition, teachers and students must also share ideas to find other interesting kinds of ways in English speaking learning.